Academic Stress Reviewed from Self-Adjustment, Learning Saturation, and Grit - Hairani Lubis; Monika Oktafia; Anindya Pinasthi Putri (Indonesian Journal Of Educational Research and Review, 2022)
The condition of the Covid-19 pandemic has changed the learning process into E-Learning at home, but academic demands have not changed. Instead, they have increased to the point where students experience academic stress. This academic stress certainly impacts student learning motivation which becomes low. This research analyzed academic stress regarding self-adjustment, learning saturation, and grit. This type of research is quantitative. The subjects in this study were 100 Psychology students. Data were collected using a Likert scale, namely the self-adjustment scale, the learning saturation scale, and the grit scale. The technique used to analyze the data in multiple regression analysis with the help of the JASP 0.16 application. The study results showed that self-adjustment, learning saturation, and grit affect academic stress simultaneously. The adjustment variable has a significant positive effect on academic stress. Saturation of learning affects academic stress in a positive and significant way. Furthermore, grit also has a significant negative effect on academic stress. It can be concluded that self-adjustment, learning saturation, and grit affect academic stress.